PERLINDUNGAN TERHADAP PENGUNGSI DOMESTIK MENURUT HUKUM HUMANITER DAN HAK ASASI MANUSIA - Yuliantiningsih, Aryuni (Jurnal Dinamika Hukum, 2008)
Internal displacement is one of humanitarian problem that need to be handled in accordance to humanitarian principles.  The usual causes of internal displacement are, as results of armed conflicts, violations of human rights, and natural disaster. Internal displacement is different with refugees. For refugees who crossed border to another  country there was a protection has been regulated under The Convention relating to The Status of Refugees 1951, but for Internally Displaced Persons remain within their own countries without legal protection under international law.  To fulfill this vacuum, United Nations has stipulated a Guiding Principle on Internal Displacement in 2001.This guidance is can promote international humanitarian law and human rights law. Kata kunci: pengungsi domestik, perlindungan, hukum humaniter dan hak asasi manusia